2018
DOI: 10.1111/tbed.13072
|View full text |Cite
|
Sign up to set email alerts
|

Porcine reproductive and respiratory syndrome virusNADC30‐like strain acceleratesStreptococcus suisserotype 2 infection in vivo and in vitro

Abstract: Porcine reproductive and respiratory syndrome (PRRS), an economically significant pandemic disease, commonly results in increased impact of bacterial infections, including those by Streptococcus suis (S. suis). In recent years, PRRS virus (PRRSV) NADC30‐like strain has emerged in different regions of China, and coinfected with S. suis and PRRSV has also gradually increased in clinical performance. However, the mechanisms involved in host innate responses towards S. suis and their implications of coinfection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Consequently, the mucosal barrier is the first line of defence of the host against this pathogen. In swine, colonisation of the upper respiratory tract by S. suis may lead to an asymptomatic carriage but is also considered the first step for the development of an invasive disease, particularly in the context of coinfections with porcine respiratory viruses or polymicrobial infections [34][35][36][37][38][39][40][41][42].…”
Section: Virulence Factors and Pathogenesis Of The Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the mucosal barrier is the first line of defence of the host against this pathogen. In swine, colonisation of the upper respiratory tract by S. suis may lead to an asymptomatic carriage but is also considered the first step for the development of an invasive disease, particularly in the context of coinfections with porcine respiratory viruses or polymicrobial infections [34][35][36][37][38][39][40][41][42].…”
Section: Virulence Factors and Pathogenesis Of The Infectionmentioning
confidence: 99%
“…Numerous examples of coinfections with common swine viruses such as PRRSV, SwIV, porcine circovirus (PCV), and PRCV have been detected in the diagnostic lab and investigated experimentally, and coinfections with these viruses generally result in a more severe clinical disease outcome [115][116][117][118]. Similarly, coinfections with the viruses mentioned above and common swine bacterial pathogens have often shown that these viruses are potent initiators of secondary bacterial infections [34][35][36][37][38][39][40][41][42]. Primary bacterial pathogens can also predispose to secondary bacterial colonisation and disease.…”
Section: Appendix E Proceeding From the 4th International Workhop On Streptococcus Suismentioning
confidence: 99%
“…are often present in healthy animals, significant disease can result, most commonly associated with S. suis ( MacInnes et al, 2008 ; USDA, 2016 ). Infection with PRRSV has been shown to increase susceptibility to S. suis infection ( Thanawongnuwech et al, 2000 ; Li et al, 2019 ). Systemic infections (sepsis or septicemia) result in multiple disease processes, including meningitis, polyserositis (epicarditis, pleuritis, and peritonitis), synovitis, arthritis, endocarditis, encephalitis, abortions, and abscesses ( Staats et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although this study only considers the relationship between pseudorabies and bacteria, CSF, PRRS and PCV2 also cause immune‐suppression and may induce similar results. It has been reported that PRRSV accelerates S. suis or H. parasuis infection in vivo and in vitro, and also causes more severe respiratory symptoms (Yu et al., 2012; Huong et al, 2016; Li et al., 2017, 2018) among pigs with clinical symptoms of respiratory diseases, the highest percentage of PCV2 infection was with P. multocida in all cases (Kim et al., 2003), pigs infected with PCV2 and PRRSV suffer from severe immune‐suppression, so it's easy for occurrence of secondary bacterial infection(Chang, Peng, Chang, Chaung, & Chung, 2008; Opriessnig et al., 2011; Wang et al., 2019). Also, the poor biosecurity and husbandry can cause more bacterial infection.…”
Section: Discussionmentioning
confidence: 99%